Atomistic simulation of the uniaxial tension of black phosphorene nanotubes - Nguyen, Van-Trang; Nguyen, Danh-Truong; Le, Minh-Quy (Vietnam Journal of Mechanics, 2018)
In the present work, the uniaxial tensile tests of 3 pairs black phosphorene nanotubes are simulated by molecular dynamics finite element method with Stillinger-Weber potential. Each pair contains an armchair black phosphorene nanotube and a zigzag one, which have approximately equal diameters. Three armchair black phosphorene nanotubes, namely (0, 15), (0, 19) and (0, 21); and three zigzag black phosphorene nanotubes, namely (20, 0), (26, 0) and (28, 0), are considered. We found that the Young's modulus of these tubes increases when their diameter increases. Their fracture stress and fracture strain are also investigated.